Studying the effectiveness of some locally isolated bacteria groups in biogas production (Latakia University Journal -Biological Sciences Series, 2022)
The research aimed to study the effect of adding several bacterial groups on the amount of biogas which is produced during the anaerobic fermentation of cow dung (pH = 6.76, MC = 79.85 TS = 20.15%, VS = 87.49%, C/N = 21.67). The first group T1: raw cow dung which has not added any bacteria. The second group T2: Lactobacillus acidophilus, Bacillus cereus, Bacillus subtilis, Sphingobacterium alimentarium, Micrococcus varians. The third group T3: Pseudomonas aeruginos, Proteus mirabilils, E.coli, Streptococcus pneumonia. The fourth group T4: Methanobacterium sp. The fifth group T5 includes all the previous species. The experiment was designed in a completely randomized method with three replications. Results show that the amount of biogas produced was (13161.33, 14286.33, 14638.5, 15209.33, 16575.33) ml, respectively. Whereas, the fifth group significantly outperformed all other groups. So, it can be said that adding all types of inoculum together has an effective role in increase the amount of biogas.